Pain in Children With Burns - Ana Kelve Castro Damasceno; Paulo César de Almeida; Maria Grasiela Teixeira Barroso (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Our objective is to identify the epidemiological profile of children that are victims of burn in the pain process and evaluate the pain in burnt children using a Visual Scale - EV (scale of faces). It is a study with an epidemiological and descriptive nature that was developed in a Centre of Treatment of Burnt of the Ceará State in the period between August, 2003 and September, 2004. Our sample is composed of 100 children. We use a form in which we have the Visual Scale - EV (scale of faces). During the evaluation with EV, we observe by comparing the evaluation made by the child and the one made by the carer that, in most levels of pain, the evaluation made by the child had a greater value than the one made by the carer. However, in levels 0 (no pain), 3, 4 and 5 (the worst level) it was 50% for each evaluator, what demonstrates the adult had a good evaluation of the pain of the child in hospital. It shows they know well their children. May the pain evaluation become part of the daily routine of Nursing care, affirming itself as the fifth vital signal.